Cashew India: an exclusive android application for cashew cultivation - Mohana, G. S.; Nayak, M. G.; Gajbhiye, R. C.; Menon, Jalaja S.; Rao, Uma Maheshwar; Ramteke, Vikas; Poduval, Mini; Desai, S.K.; Velmurugan, S.; Panda, P.K.; Deshmukh, N. A. (Journal of Plantation Crops, 2025)
Smartphones and their apps have become integral to communication through voice, text, and video. Consequently, numerous crop-related apps developed by public and private organizations are deployed to effectively disseminate agricultural information and technologies. ICAR- Directorate of Cashew Research is the nodal centre in the country for cashew research and continuously generates new information on cashew cultivation and other aspects. The data on various aspects of cashew cultivation available in the institute has been utilized to develop the Cashew India app. This app gives comprehensive information on cashew cultivation aspects, statistics, markets, economics, success stories, services, and training, aiming to empower different stakeholders of the crop. The efforts and technologies behind the development of this app and its uniqueness among the various apps developed for different crops are elucidated here. The principles adopted in this app can be profitably extended to overcome the inadequacy of existing crop-related apps or to create new ones by the agencies involved in app development.